The effect of oral hygiene training on plaque index in visually impaired school children - Firoozeh Nilchian; Shiva Mortazavi; Maryam Kashani (Tehran University of Medical Sciences, 2020)
Background and Aims: Dental caries is a common childhood disease with a considerable effect on quality of life. In visually imparted children oral health and dental treatments are more complicated. To prevent oral diseases, it is necessary to educate visually impaired children. The aim of this study was to evaluate the effects of oral hygiene training on oral health status in visually impaired children. Materials and Methods: In this semi experimental study, 50 visually impaired children 8 to 12 years old were systematically recruited from visually impaired exceptional schools. Participants were randomly allocated into two control and study groups (25 each). Sillness and Loe plaque index was recorded in all 50 children at baseline and after intervention and follow up periods. The study group received oral hygiene instructions (rolling toothbrush technique) using Braille booklets and hand over hand education. The training repeated three times with two weeks' intervals and at the end Plaque Index was measured in both groups ANOVA, T-test and Mann Whitney tests were employed to compare intra and inter groups statistical analyses. (α=0.05). Results: At the baseline, the mean plaque index score in the study group was 2.03±0.52 which decreased to 1.23±0.34 at the end of the intervention (P<0.001). Initially, in control group, the Plaque Index score was 2.26±0.49 which was 2.19±0.44 at the end of the study. Changes in Plaque Index scores were statistically significant between two groups. (P<0.001). Conclusion: It was concluded that oral hygiene instructions using visually impaired specific training methods improved Plaque Index in these children.